Vulnerabilities in SBAS and RTK Positioning in Intelligent Transport Systems: An Overview - Imparato, D.; El-Mowafy, Ahmed; Rizos, C.; Wang, J. (2018)
As Intelligent Transport Systems (ITS) become more automated and more demanding, ITS positioning integrity is becoming a key performance parameter. ITS relies on GNSS technology for absolute positioning. In order to develop efficient models and methods that can provide high levels of integrity, it is necessary to study the vulnerabilities of the GNSS-based positioning systems intended for use in ITS applications, in particular those which require positioning accuracy at the sub-metre level. These vulnerabilities are attributed to several sources and include biases and errors in the GNSS measurements, and in the corrections applied to the measurements for augmented performance, as well as those induced by the operating environment. The vulnerabilities also comprise possible anomalies that may affect each component of the system, including disturbances or disruption in the communications between the service provider and users, data latency, to name a few. In this paper a preliminary overview of possible vulnerabilities is presented for two widely-used GNSS positioning techniques envisioned for ITS applications: the Satellite-Based Augmentation System (SBAS) and low-cost RTK. Some examples are given, including the source of these errors, e.g. satellite or receiver hardware, environment, external communications, the error magnitude, temporal and spatial behaviour, their deterministic and stochastic characteristics, and their impact on estimated positions. Furthermore, some of the corresponding mathematical models that can be used to describe these vulnerabilities in the integrity monitoring algorithms are presented.